Increased HIF-2α activity in the nucleus pulposus causes intervertebral disc degeneration in the aging mouse spine - Johnston, Shira N.; Tsingas, Maria; Ain, Rahatul; Barve, Ruteja A.; Risbud, Makarand V. (Frontiers in Cell and Developmental Biology, 2024)
Hypoxia-inducible factors (HIFs) are essential to the homeostasis of hypoxic tissues.Although HIF-2α, is expressed in nucleus pulposus (NP) cells, consequences of elevated HIF-2 activity on disc health remains unknown. We expressed HIF-2α with proline to alanine substitutions (P405A;P531A) in the Oxygen-dependent degradation domain (HIF-2αdPA) in the NP tissue using an inducible, nucleus pulposus-specific K19 CreERT allele to study HIF-2α function in the adult intervertebral disc. Expression of HIF-2α in NP impacted disc morphology, as evident from small but significantly higher scores of degeneration in NP of 24-month-old K19 CreERT ; HIF-2α dPA (K19-dPA) mice. Noteworthy, comparisons of grades within each genotype between 14 months and 24 months indicated that HIF-2α overexpression contributed to more pronounced changes than aging alone. The annulus fibrosus (AF) compartment in the 14month-old K19-dPA mice exhibited lower collagen turnover and Fourier transform-infrared (FTIR) spectroscopic imaging analyses showed changes in the biochemical composition of the 14-and 24-month-old K19-dPA mice. Moreover, there were changes in aggrecan, chondroitin sulfate, and COMP abundance without alterations in NP phenotypic marker CA3, suggesting the overexpression of HIF-2α had some impact on matrix composition but not the cell phenotype.Mechanistically, the global transcriptomic analysis showed enrichment of differentially expressed genes in themes closely related to NP cell function such as cilia, SLIT/ROBO pathway, and HIF/Hypoxia signaling at both 14-and 24-months. Together, these findings underscore the role of HIF-2α in the pathogenesis of disc degeneration in the aged spine.